How leisure involvement impacts visitors’ perceived health benefits in urban forest parks: examining the moderating role of place attachment - Zhou, Wei; Fan, Shaozhen; Wu, Yuanjing; Wang, Guangyu; Lan, Siren (Frontiers in Psychology, 2024)
Urban forest park leisure is a significant means for residents to achieve health and well-being, thus possessing high public health value. However, the relationship between visitors' leisure involvement and perceived health benefits has not been clarified. This study introduced restorative experiences and positive emotions as mediators and place attachment as a psychological moderator, innovatively constructing a stimulus-organism-response-moderator (SORM) integrated model. This moderated mediation model aimed to examine the mechanism through which visitors' leisure involvement influenced perceived health benefits. A field survey was conducted in Fuzhou National Forest Park in Fujian, China, resulting in the collection of 588 valid questionnaires. The results showed that visitors' leisure involvement positively impacted restorative experiences and positive emotions. Restorative experiences and positive emotions completely mediated the indirect relationship between visitors' leisure involvement and perceived health benefits. Place attachment enhanced the impact of restorative experiences on perceived health benefits, thereby positively moderating the mediation effect of restorative experiences. Place attachment also diminished the impact of positive emotions on perceived health benefits, thereby negatively moderating the mediation effect of positive emotions. Therefore, significant differences existed in the psychological processes involved in acquiring perceived health benefits among visitors with different levels of place attachment. Our findings might enrich the existing knowledge of place attachment and forest health benefits, providing valuable references for designing and optimizing urban forest parks.